Role of angiotensin peptides in risk stratification and prognostication for heart failure: focus on plasma Ang 1–7/Ang II ratio. (25th November 2020) - Wang, K; Basu, R; Poglitsch, M; Bakal, J.A; Oudit, G.Y
Abstract: Background: ACE2 and Ang 1–7 are endogenous negative regulators of the renin-angiotensin system (RAS) exerting cardioprotective effects in models of heart failure (HF). Recombinant ACE2 markedly increased plasma Ang 1–7 and lowered Ang II levels in clinical trials. Elevated plasma ACE2 activity is associated with adverse outcomes in HF patients. However, the direct effects of systemic and tissue ACE2 activation on angiotensin peptides in relation to long-term HF outcomes has yet to be examined. Purpose: To generate insights into the ACE2 mediated cardioprotective arm through the relative levels of its substrates and products using the plasma Ang 1–7/Ang II ratio, and assess its prognostic utility in HF patients. Methods: 110 HF patients were prospectively enrolled from outpatient clinics and the emergency department. Comprehensive circulating and equilibrium levels of plasma angiotensin peptides were assessed using novel liquid chromatography-mass spectrometry/mass spectroscopy techniques. Plasma aldosterone, BNP, active renin activity and clinical profiles were captured at baseline. Patients were stratified into above and below median cohorts based on equilibrium and circulating levels of Ang 1–7/Ang II ratio, as a surrogate for ACE2 functionality. During a median follow-up of 5.1±0.8 years, composite clinical outcomes were assessed through all-cause in-patient hospitalizations and mortality. Results: Circulating and equilibrium angiotensin peptide levels strongly correlated in our patient cohort. All-cause mortality for HF patients with equilibrium Ang 1–7/Ang II ratios above the median showed higher survival rates compared to below median patients (76.4% vs. 50.9%; p=0.004); similar results were observed for circulating Ang 1–7/Ang II ratios (72.7% vs. 54.5%; p=0.041). Adjusting for covariates, elevated equilibrium (HR: 0.24; 95% CI: 0.09 to 0.69; p=0.008) and circulating (HR: 0.35; 95% CI: 0.13 to 0.94; p=0.036) Ang 1–7/Ang II ratios was associated with improved survival. Lower hospitalization duration was also associated with elevated equilibrium (p<0.001) and circulating (p=0.023) Ang 1–7/Ang II ratios. In nested models, net reclassification analysis showed considerable improvement in risk prediction for all-cause mortality at 5 years provided by both the equilibrium (+45.0% [95% CI: 7.3% to 82.7%]) and circulating Ang 1–7/Ang II ratios (+24.3% [95% CI: 0.4% to 59.6%]) respectively. Conclusions: We extensively profiled plasma angiotensin peptides in HF patients and identified elevated ACE2 signature, reflected through the Ang 1–7/Ang II ratio, as an independent and incremental predictor of beneficial outcomes, higher survival rate, and decreased hospitalization duration. These findings provide important clinical evidence supporting strategies aiming to promote the beneficial ACE2/Ang 1–7/Mas receptor axis concurrent with RAS blockade therapies inhibiting the detrimental ACE/Ang II/AT1 receptor axis. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Alberta Innovates, Canadian Institute of Health Research